2022
DOI: 10.1039/d2ja00032f
|View full text |Cite
|
Sign up to set email alerts
|

Method development for speciation analysis of silver nanoparticles and silver ions in green algae and surface waters at environmentally relevant concentrations using single particle ICP-MS

Abstract: Interactions of silver(I) and PVP-stabilized silver nanoparticles (AgNPs) of different nominal diameters (40, 60 and 75 nm) with green microalgae Desmodesmus subspicatus during 24 h incubation period in matrices that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Thus, with the particle-size calibration method, any change in nebulized aerosol transport efficiency or absolute sensitivitieseither from a changing sample matrix or from driftwill result in an inaccurate mass quantification. To improve the accuracy of particle quantification, approaches based on internal standardization, , standard addition, isotope dilution, , and matrix-matched standards have been used. Here, we demonstrate the use of online microdroplet calibration (Figure ) as an accurate calibration strategy for spICP-TOFMS that eliminates the need for exhaustive sample preparation and matrix removal procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with the particle-size calibration method, any change in nebulized aerosol transport efficiency or absolute sensitivitieseither from a changing sample matrix or from driftwill result in an inaccurate mass quantification. To improve the accuracy of particle quantification, approaches based on internal standardization, , standard addition, isotope dilution, , and matrix-matched standards have been used. Here, we demonstrate the use of online microdroplet calibration (Figure ) as an accurate calibration strategy for spICP-TOFMS that eliminates the need for exhaustive sample preparation and matrix removal procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Jiménez-Lamana et al [ 15 ] used cysteine to stabilize Ag(I) and Triton X-100 as a surfactant to stabilize AgNPs. The use of surfactants was reported in other studies [ 22 , 24 , 25 ] to prevent the loss of NPs and to recover the total spiked Ag. Gao et al [ 24 ] also studied the process of sample grinding and concluded that it improved NP extraction leading to recoveries of nearly 100% for gold nanoparticles in mice organs.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, enzymatic extraction is conducted using proteinase K [ 26 ], but this enzyme can partially dissolve AgNPs, and the presence of matrix residues leads to a lower nanoparticle recovery [ 17 ]. Comparisons between alkaline and enzymatic extractions were reported [ 25 , 27 ], obtaining better results with the alkaline extraction. Sung et al [ 27 ] observed that TMAH gave higher recoveries (102%) than enzymatic extraction (74%) for the extraction of AgNP and AuNP from zebrafish liver samples.…”
Section: Introductionmentioning
confidence: 99%
“…34 nm for lysates of green algal cells). 7 This can be overcome by application of hyphenated techniques, such as HPLC-ICP-MS, which enable detection of smaller particles (from ∼1 nm). The chromatographic separation of the nano and dissolved forms of silver was performed on a reversed-phase column (Nucleosil C 18 ) with relatively wide pore sizes (1000 Å and 4000 Å) [8][9][10] or amino column (Venusil Durashell-NH 2 ) with pore sizes of 500 Å and 1000 Å.…”
Section: Introductionmentioning
confidence: 99%